Research progress of transcranial direct current stimulation for post-stroke aphasia - Shu XU; Hong-yu LI; Xiao-xia DU; Lu-ping SONG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
Transcranial direct current stimulation (tDCS), which is a safe and noninvasive method for inducing or enhancing neural plasticity, can promote the recovery of post-stroke aphasia (PSA). This paper explores the possible mechanisms of verbal recovery in patients with PSA, and analyzes the role of bilateral hemispheres and cerebellum in speech recovery to review the research progress of application of tDCS in PSA.